Evaluation of antifungal activity of three essential oils against selected isolates of Penicillium, Purpureocillium and Acremonium - Kręcidło, Łukasz; Krzyśko-Łupicka, Teresa (Ecological Questions, 2018)
Storage is a critical process of food production because incorrect conditions during this process lead to the growth of economic costs caused by material loss. It is important to maintain adequate microbiological purity of storage areas. The development of microbes present in warehouses may lead to secondary contamination of stored materials and reduce their quality. The aim of the study was to evaluate the effect of essential oils on the growth of Acremonium strictum, Penicillium citrinum, Penicillium expansum and Purpureocillium lilacinum. Fungal strains were isolated from the food warehouse. Studies on the influence of selected mix of phenolic substances were performed using three commercially available essential oils, namely rosewood, rosemary and thyme. Evaluation of antifungal activity of these essential oils was done by plate dilution method and expressed as inhibition rate of mycelial growth and index of mycelial growth, and by minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) assays. Thyme oil showed the highest antifungal activity and inhibited growth of all fungal strains at the lowest tested concentration (1 μL mL-1). Penicillium expansum strain was found to be the most resistant to the tested essential oils.